Indeterminate skeletal and lymph node lesion on 18F PSMA 1007 PET/CT scanning: lessons from a review at 12 months with PSMA-RADS. Issue 9 (14th July 2022) - Bhoil, Amit; Seshadri, Nagabhushan; Vinjamuri, Sobhan
Abstract : Aims of the study: The study utilizes the prostate-specific membrane antigen-reporting and data system (PSMA-RADS) version 1.0 in a real-world patient scenario in the evaluation of equivocal lesions using the PSMA-RADS categorization for patient management and communication in multidisciplinary team (MDT) meetings. Methods: A retrospective analysis of 203 patients who had 18F PSMA PET/CT for either restaging or staging over 12 months was undertaken. The scans were evaluated for local disease, lymph node involvement and distant metastases. The scan findings were classified as suspicious for metastases, and equivocal and benign lesions. Experience with PSMA ligand imaging was considered while classifying the lesions, equivocal lesions were assessed with PSMA-RADS and followed up with complementary imaging and/or clinical follow-up assessment or MDT for further patient management. Results: A total of 91 of 203 patients had equivocal lesions. Follow-up assessment was performed in 47 of 91 patients with imaging ( n  = 36) or MDT discussion ( n  = 11). On follow-up imaging ( n  = 36), equivocal lesion was seen in skeletal lesions ( n  = 24), pelvic lymph nodes ( n  = 6), both skeletal and pelvic nodes ( n  = 4), hilar and mediastinal lymph nodes ( n  = 1) and spleen ( n  = 1). The patients were reclassified as benign, metastatic with few lesion remained equivocal. Overall follow-up assessment impacted clinical management in 47% patients. Conclusion: 18F PSMA PET/CT may show equivocal lesions; many of them in the skeleton, a small proportion of which are ultimately proven metastatic. In contrast, a higher proportion of the equivocal nodes in the pelvis end up being metastatic on follow-up. A structured reporting with PSMA-RADS grading helps in the proper classification of lesions and standardization of reports.